A Study Evaluating Rational Drug Use In Malaria Management Among Public And Private Healthcare Facilities At Two Pakistan Cities - Malik, Madeeha (2013)
Malaria continues to be a major public health issue in Pakistan, due to socioeconomic and epidemiological reasons. The thesis aimed to assess current scenario related to rational drug use, knowledge, perceptions and adherence of prescribers with standard treatment guidelines for malaria in public and private healthcare facilities in two cities of Pakistan; Islamabad (national capital) and Rawalpindi (twin city). A combination of quantitative and qualitative research methods were used for data collection. The perceptions’ of malaria control program officials, prescribers and hospital pharmacists regarding factors affecting rational treatment practices for malaria were explored by conducting semi-structured interviews. Simple random sampling technique was used to draw the sample of public and private tertiary (n = 20), secondary (n = 10), primary (n = 20) healthcare facilities and community pharmacies from Islamabad (n = 118) and Rawalpindi (n=120) respectively. Besides that, a sample of 360 prescribers was selected randomly from the two cities (n = 180 each city). Prescribing practices were evaluated by assessing prescriptions for malaria using WHO prescribing indicator form while a structured questionnaire was used to assess the perceptions and knowledge of prescribers regarding standard treatment guidelines. United State Agency for International Development (USAID) stock out form and questionnaire were use to review drug availability and process of drug management respectively. Simulated visits were also performed to observe disease case management of malaria at community pharmacies.